Identification of putative genetic modifying factors that influence the development of Papillon–Lefévre or Haim–Munk syndrome phenotypes. (9th March 2020) - Pap, É. M.; Farkas, K.; Tóth, L.; Fábos, B.; Széll, M.; Németh, G.; Nagy, N.
Summary: Background: Papillon–Lefévre syndrome (PLS; OMIM 245000) and Haim–Munk syndrome (HMS; OMIM 245010), which are both characterized by palmoplantar hyperkeratosis and periodontitis, are phenotypic variants of the same disease caused by mutations of the cathepsin C ( CTSC ) gene. Aim: To identify putative genetic modifying factors responsible for the differential development of the PLS or HMS phenotypes, we investigated two Hungarian patients with different phenotypic variants (PLS and HMS) but carrying the same homozygous nonsense CTSC mutation (c.748C/T; p.Arg250X). Methods: To gain insights into phenotype‐modifying associations, whole exome sequencing (WES) was performed for both patients, and the results were compared to identify potentially relevant genetic modifying factors. Results: WES revealed two putative phenotype‐modifying variants: (i) a missense mutation (rs34608771) of the SH2 domain containing 4A (SH2D4A) gene encoding an adaptor protein involved in intracellular signalling of cystatin F, a known inhibitor of the cathepsin protein, and (ii) a missense variant (rs55695858) of the odorant binding protein 2A (OBP2A) gene, influencing the function of the cathepsin protein through the glycosyltransferase 6 domain containing 1 (GLT6D1) protein. Conclusion: Our study contributes to the accumulating evidence supporting the clinical importance of phenotype‐modifying genetic factors, which have high potential to aid the elucidation of genotype–phenotype correlations and disease prognosis.